حماية الملكية الفكرية في الفقه الإسلامي والقانون الوضعي: دراسة مقارنة على الرسوم المتحركة لستوديو جيبلي (Studio Ghibli): دراسة مقارنة على الرسوم المتحركة لستوديو جيبلي - Syafiq, Naufal; Imam Sujoko; Mualimin Mochammad Sahid (Universitas Islam Indonesia, 2026)
This study aims to analyze the protection of intellectual property rights in animated works, while identifying the underlying factors that motivated the selection of this topic, particularly the increasing prevalence of digital piracy and its impact on creative industries. It also seeks to examine the extent to which Islamic jurisprudence is compatible with positive law in protecting these rights. The study adopts a qualitative research approach using a comparative framework between Islamic jurisprudence and positive law. It also employs a descriptive-analytical method to examine textual data derived from primary sources, such as classical and contemporary fiqh literature and legal regulations, as well as secondary sources including academic studies, with reference to the theory of maqāṣid al-sharīʿah as an analytical framework. The findings indicate that Islamic jurisprudence recognizes intellectual property as a form of intangible property that must be protected, and that it converges with positive law in affirming legal protection. However, practical challenges remain, particularly in the digital environment, where piracy continues to spread. This study is distinguished by its integration of juristic analysis with practical application through a case study of Studio Ghibli’s works, thereby offering a contemporary analytical model that bridges theory and practice in intellectual property issues.